The College of The Bahamas in Research: A Process in Motion - Walker, Berthamae L. (International Journal of Bahamian Studies, 2015)
Though not previously thought of as a “research” institution, much has been written or published about the College of the Bahamas by past and present faculty and students as well as scholars not associated with the institution. To what extent, though, are researchers publishing about the College of The Bahamas and what percentage are published in the College’s research journals as opposed to elsewhere? The focus of this article is on a select body of research published over the past 40 years by the College of The Bahamas research journals and publications as noted in the ProQuest database in which the college is the subject of the research.